2007
DOI: 10.1063/1.2434160
|View full text |Cite
|
Sign up to set email alerts
|

Modeling microscopic swimmers at low Reynolds number

Abstract: The authors employ three numerical methods to explore the motion of low Reynolds number swimmers, modeling the hydrodynamic interactions by means of the Oseen tensor approximation, lattice Boltzmann simulations, and multiparticle collision dynamics. By applying the methods to a three bead linear swimmer, for which exact results are known, the authors are able to compare and assess the effectiveness of the different approaches. They then propose a new class of low Reynolds number swimmers, generalized three bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
96
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 34 publications
11
96
1
Order By: Relevance
“…Similar nonequilibrium properties have been studied for colloids [7,[20][21][22][23][24][25][26], polymers [19,[27][28][29][30][31][32][33][34], vesicles [35], and cells [36,37] in flow fields, colloids in viscoelastic fluids [38], as well as for self-propelled spheres [39][40][41], rods [3,42], and other swimming objects [43][44][45]. Moreover, extensions have been proposed for fluids with nonideal equations of state [46] and mixtures [47].…”
Section: Introductionmentioning
confidence: 99%
“…Similar nonequilibrium properties have been studied for colloids [7,[20][21][22][23][24][25][26], polymers [19,[27][28][29][30][31][32][33][34], vesicles [35], and cells [36,37] in flow fields, colloids in viscoelastic fluids [38], as well as for self-propelled spheres [39][40][41], rods [3,42], and other swimming objects [43][44][45]. Moreover, extensions have been proposed for fluids with nonideal equations of state [46] and mixtures [47].…”
Section: Introductionmentioning
confidence: 99%
“…Equations (7,8) were integrated using the semi-implicit method (see appendix B) for a one-dimensional system using periodic boundary conditions. As the initial condition, the flat interface with a uniform machine distribution was chosen and small random initial perturbations were applied.…”
Section: Numerical Investigations Of the Nonlinear Regimementioning
confidence: 99%
“…Generally, it can be shown that any physical object, cyclically changing its shape in such a way that the internal forward and back motions are different, propels itself through the liquid [3,4]. Elementary models of such swimmers, constructed by joining together mobile links [3,5] or by connecting a few spheres by several actively deformable links [6,7,8], have been considered. Typically, the concept of molecular swimmers is applied to explain active motion of bacteria and other microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of micro-robots represent a flourishing modern research topic that strives to create a fundamental base for modern applications in medicine and technology, see Purcell (1977), Becker, Koelher & Ryder (2003), Najafi & Golestanian (2004), Dreyfus et al (2005), Chang et al (2007), Earl et al (2007), Alouges, DeSimone & Lefebvre (2008), Golestanian & Ajdari (2008, 2009, Leoni et al (2009), Alexander, Pooley & Yeomans (2009), Gilbert et al (2010) and Lauga (2011). The simplicity of the geometry represents the major advantage in studies of micro-robots (in contrast with the extreme complexity of self-swimming micro-organisms, e.g.…”
Section: Introductionmentioning
confidence: 99%